PH-tunable gradients of wettability and surface potential - Mierczynska, A.; Michelmore, A.; Tripathi, A.; Goreham, R.; Sedev, Rossen; Vasilev, K. (RSC Publishing, 2012)
Smart materials that can sense and respond to changes in the environment are of interest in numerous and diverse applications. In this paper, we report gradient surfaces where wettability and surface potential respond to changes in the pH. The gradients are produced by controlling the concentration of amine and carboxyl acid groups across the surface. The response of surface wettability to pH changes was studied by water contact angle measurements. The potential across the surface was determined by atomic force microscopy-based surface force measurements. These studies showed that at low pH the surface potential changes from "no charge" at the acid end to a positive charge at the amine end. At high pH the surface potential changed from negative at the acid end to "no charge" at the amine side. At an intermediate pH the charge across the surface changes from negative at the acid end to positive at the amine end. Potential applications include separation or guidance of charged entities such as particles, proteins or bacteria.